The Effects of Objective Economic Pressure and Coping Strategies on Fisherman Family Vulnerability - Ghaida Salma; Euis Sunarti (Journal of Child, Family, and Consumer Studies, 2025)
Fisherman families experience objective economic pressure due to unstable income, thus requiring coping strategies to avoid family vulnerability. This study aims to analyze the influence of objective economic pressure and coping strategies on the vulnerability of fisherman families. The study employed a cross-sectional design involving 105 intact fisherman families with school-age children in Muara Angke Fishing Village, North Jakarta, selected through purposive sampling. The data were analyzed using descriptive statistics, correlation analysis, and path analysis. The correlation analysis showed that the husband’s years of education were significantly and negatively related to objective economic pressure. Per capita income was significantly and negatively associated with objective economic pressure, coping strategies, and family vulnerability. Family size was significantly and positively associated with objective economic pressure. Objective economic pressure was significantly and positively associated with coping strategies and family vulnerability, while coping strategies were significantly and negatively associated with family vulnerability. The path analysis revealed that per capita income had a significant direct negative effect on objective economic pressure. Furthermore, per capita income had significant indirect negative effects on coping strategies and family vulnerability through objective economic pressure. Objective economic pressure had significant positive direct effects on both coping strategies and family vulnerability. Based on the findings, fisherman families are recommended to seek additional income sources, maintain assets, save money, avoid conflicts, and share household responsibilities among family members